Laws of the City of Johnstown, Pa., Embracing City Charter, Act of Assembly of May 23, 1889, for the Government of Cities of the Third Class, General and Special Ordinances, Rules of Select and Common Councils and Joint Sessions, at 84, General Ordinance no. 2, § 2 (1897) - (:unkn) unknown (General Publisher, 1897)
Any person who shall on any public street, alley, square, or public grounds, within the limits of the city, willfully discharge any gun or firearm - excepting in necessary defense of self or property - or shall wantonly throw any metal, stone, brick, bullet, or other missile, or who shall willfully explode any torpedo, bomb, fire-cracker, or fire-works in any place on either public or private grounds, or on the street corners or alleys, shall upon conviction pay a fine of not less than one dollar or more than fifty dollars with costs.
--
Keywords: DISCHARGE